Atezolizumab-induced sarcoid-like granulomatous reaction in a patient with urothelial cell carcinoma. (17th October 2018) - Mitchell, Michael A; Hogan, Kevin; Amjadi, Kayvan
A 61-year-old woman with locally advanced, high-grade urothelial cell carcinoma was treated with the anti-programmed death-ligand 1 antibody atezolizumab. She initially received neoadjuvant chemotherapy and surgery that led to clinical and radiographic remission at the time of atezolizumab initiation. Within 3 months she developed new mediastinal and hilar lymphadenopathy as well as pulmonary nodules in a pattern characteristic of pulmonary sarcoidosis. Mediastinal lymph node biopsy by endobronchial ultrasound demonstrated noncaseating granulomas without evidence of malignancy or infection. Within 4 weeks of initiation of prednisone and cessation of atezolizumab there was marked reduction in intrathoracic lymphadenopathy and perilymphatic nodules. This is the first reported case of atezolizumab-induced sarcoid-like granulomatous reaction.